Costa Rica: Golden Opportunity for 1989 - Richard Keith Corbin (Society for Mining, Metallurgy & Exploration, 1988)
INTRODUCTION With the world media full of predictions that the price of gold will quadruple in three years (Maybury, R.J., 1988), and with financial forecasters and strategists touting opportunities to make 400% in gold (Skousen, M., 1988), explorationists and entrepreneurs are scurrying to find enough gold to feed the global gold fever created. At the same time, gold deposits in the United States and other developed and intermediate countries are becoming less attractive because of environmental restrictions, radical reductions in tax incentives, and depleting reserves, causing people in the mining industry to begin looking at opportunities for foreign investment in gold mining concessions in lesser developed countries (LDCs). Meanwhile, LDCs are responding with chamber-of-commerce aplomb in marketing their opportunities. In the face of all this frenzy and hype, targeting gold mining concessions in LDCs for foreign investment may be done more objectively by employing a systematic approach. For this paper the SHOP rating system (Corbin, R.K., 1987), which considers factors of the LDC's stability, hospitability, ore occurrence, and profitability potential is used. The result is that a tiny banana-growing republic in Central America, first discovered by Columbus and named the "Rich Coast'' because of the many gold adornments worn by its Indians, has been rediscovered and emerges as a classic LDC gold target.